The Oracle of Gog and Magog: A Social-Rhetorical Interpretation of The Prophetic Discourse in Al-Kahf 83-101 - Mowafg Abrahem Abrahem Masuwd; Sahiron Syamsuddin; Robert Setio (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2019)
As a prophetic narrative, Gog and Magog oracle has a strong influence over many Islamic sects and groups. The analysis and interpretation of God’s message within this oracle is a necessity to understand the social, cultural and literary influence of the narrative on religious and non-religious communities. By applying the socio-rhetorical interpretation (intertexture texture), readers can gain more awareness the prophetic discourse which is a part of Allah message to humanity. The main focus of the analysis is the inner texture.